Effect of temperature on exercise metabolism, hypoxia tolerance, and RNA-seq analysis in Sinilabeo rendahli from the Yangtze River, China - Li, Sheng; Guo, Hui; Du, Chun-Ying; Tao, Yi-Xi; Feng, Jing-Yun; Xu, Hao; Pang, Xu; Li, Yun (Frontiers in Ecology and Evolution, 2023)
Temperature variation affects the growth performance of fish species due to growing constraints and trade-off on physiological functions. Here we experimentally investigated several metabolic and physiological parameters in Sinilabeo rendahli, an endemic fish species found in the Yangtze River in China. After a 14-day acclimation period, we measured routine metabolic rate (RMR), individual metabolic rate (MO2), temperature quotient (Q10), loss of equilibrium (LOE), and critical oxygen tension (Pcrit) at three different temperatures (15, 20, and 25°C). Moreover, we sampled the muscle tissue from juvenile S. rendahli under experimental conditions after 28 days of acclimation and performed transcriptome-RNA sequencing (RNA-seq). The Pcrit of the fish at the above acclimation temperatures were determined to be 1.07, 1.28, and 1.33 mg·L−1, respectively, and corresponded with increasing acclimation temperatures (15–25°C). RMR was positively correlated with Pcrit (r = 0.4711, P = 0.0201), negatively correlated with LOE (r = −0.4284, P = 0.0367), and significantly positively correlated with MRcrit (r = 0.8797, P < 0.001) at temperatures ranging from 15 to 25°C. In addition, a total of 4,710 differentially expressed genes (DEGs) were identified. The results of DEG analysis and KEGG clustering analysis indicated that energy metabolism played a central role in thermal stress in S. rendahli for the major upregulated genes. This was followed by autophagy, mitophagy, cardiac muscle contraction, extracellular matrix (ECM)-receptor interaction, and protein digestion and absorption. This study is significant for understanding the adaptive response of S. rendahli to thermal stress. Even more importantly, this study demonstrates that S. rendahli is more suitable for cold-water life.